Effects of Ultrafine and Conventional Pulverization on Physicochemical Characteristics and Nutrient Content of Schizophyllum commune Powder - Xiaoli LUO; Ning YANG; Pei ZHOU; Jingjing CAO; Shasha ZHANG; Dafeng SUN (Shipin gongye ke-ji)
To investigate the effects of different grinding treatments on the physicochemical properties and nutritional component contents of Schizophyllum commune powders, two grinding methods—superfine grinding and ordinary grinding—were employed in this study. Powders with varying grinding intensities (CG-60, CG-100, CG-150, SG-20, SG-40) were prepared. The color, flowability, bulk density, hydration properties, and other physicochemical characteristics, as well as the contents of crude protein, crude polysaccharides, dietary fiber, and other nutritional components, were measured and comparatively analyzed. Results showed that ultrafine pulverization reduced the tapped density and increased the angles of slide and repose. Although flowability and fillability decreased, the ultrafine powder had a whiter and brighter color. Compared to the conventionally pulverized CG-60 powder, the SG-40 powder obtained through ultrafine pulverization showed 77.27%, 6.74%, and 11.63% higher swelling capacity, water holding capacity, and oil holding capacity, respectively. The water solubility index of SG-40 was observed to be over four times higher than that of CG-60, and the hydration properties were significantly improved (P<0.05). The crude protein, crude polysaccharides, and soluble dietary fiber contents were measured at 13.10, 10.47, and 4.27 g/100 g, respectively, which were significantly higher than those in the conventionally pulverized powder (P<0.05). In conclusion, the hydration properties and nutrient release of S. commune powder were enhanced by ultrafine pulverization. A finer texture and a whiter, brighter color were observed in the powder, although its flowability and fillability were reduced by ultrafine pulverization.